2001
DOI: 10.1053/jhep.2001.25756
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic, Renal, and Endocrine Effects of Acute Inhibition of Nitric Oxide Synthase in Compensated Cirrhosis

Abstract: To assess whether an increased production of nitric oxide is involved in the circulatory and renal alterations of cirrhosis, we evaluated systemic hemodynamics (echocardiography), renal hemodynamics, and sodium handling (lithium clearance method), plasma renin activity (PRA), aldosterone (PAC), and norepinephrine in 7 patients (3 men, mean age 65 ؎ 2 years) with compensated cirrhosis, portal hypertension, and hyperdynamic circulation during intravenous N Gmonomethyl-L-arginine (L-NMMA) (3 mg/kg bolus plus 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 65 publications
(101 reference statements)
4
38
0
1
Order By: Relevance
“…Increased nitric oxide (NO) production with resultant vasodilation has been suggested to explain the hyperdynamic systemic circulation observed in patients with cirrhosis (21)(22)(23). In HPS, investigators have documented increased NO production in the lungs (24,25), possibility mediated by endothelin receptor B signaling (26,27).…”
Section: Pathophysiology Histopathology and Mechanismsmentioning
confidence: 99%
“…Increased nitric oxide (NO) production with resultant vasodilation has been suggested to explain the hyperdynamic systemic circulation observed in patients with cirrhosis (21)(22)(23). In HPS, investigators have documented increased NO production in the lungs (24,25), possibility mediated by endothelin receptor B signaling (26,27).…”
Section: Pathophysiology Histopathology and Mechanismsmentioning
confidence: 99%
“…Therefore, genetic or pharmacological inhibition of iNOS was associated with a dramatic reduction of liver, intestine, and lung injury measured by plasma transaminase levels (Needleman and Manning, 1999). Moreover, recent results indicate that in patients with compensated cirrhosis, portal hypertension, and hyperdynamic circulation, a condition where iNOS is up-regulated (Laffi et al, 1995), acute inhibition of NO synthase corrects the altered systemic hemodynamic and improves renal function and sodium excretion (La Villa et al, 2001). Subsequent studies have revealed a similar protective effect of iNOS inhibition on bowel damage and maintenance of small bowel motility as well as preventing the gut permeability following zymosan shock (Nogawa et al, 1998).…”
Section: Nos-i Nos-ii Nos-iii Referencesmentioning
confidence: 99%
“…Diastolic dysfunction, characterized by an altered pattern of transmitral flow due to impaired diastolic relaxation of left ventricle, can be easily assessed by echocardiography and accordingly can be considered as a marker of this condition. As far as diastolic dysfunction is concerned, many etiological factors have been reliably advocated as potential pathogenic agents: notably substances as NO [18][19][20][21], TNF [22], reactive nitrogen species [23], neurohormones [24][25][26][27][28] may well affect heart structure and function along with circulatory overload [24,29] and overactivity of the SNS [30]. Thickening of heart parietal walls has been reported [12,14,17,31], nevertheless the nature of the structural changes underlying diastolic dysfunction has not been clarified so far.…”
Section: Introductionmentioning
confidence: 99%